Formulation and The Hen's Egg Chorioallantoic Membrane (HET-CAM) Test to Predict Irritation Potential of FCEE and FCEA Facial Cleansing Gel - Dina Yuspita Sari; Evi Eriani; Ibnu Afif; Erick Ferdian; Ika Ristia Rahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Limau citrus (Citrus amblycarpa (Hassk.) Ochse) peel contains vitamin C, vitamin A, flavonoids, essential oils, coumarin, and rosmarinic acid derivatives. Due to its antioxidant and antibacterial properties, it can be used as an active ingredient in facial cleansers. This study examined the quality of the ethanol fraction (FCEE) and ethyl acetate fraction (FCEA) formulas derived from C. amblycarpa peels and their irritation potential. Citrus amblycarpa peel was macerated with 96% ethanol and partitioned successively with n-hexane and ethyl acetate. The facial cleansing gel FCEE and FCEA, with concentrations of 0.20%, 0.35%, and 0.50%, respectively. The Hen's Egg Chorioallantoic Membrane (HET-CAM) method was used to determine the potential irritation. The evaluation of the FCEE and FCEA formulas showed a greenish-brownish yellow color, a distinctive aroma of C. amblycarpa, and a soft texture. The pH values ranged from 5.66 to 6.27. All formulas were homogeneous, and the viscosity values were recorded in the range of 65.33 to 91.67 dPa.s. The foam stabilities ranged from 65.94 to 69.40%, and the formulas demonstrated effective cleaning ability. The results of the HET-CAM irritation test show that the irritation score of the positive control (SLS 30%) was 12.6 (strong irritation category), that of the negative control (water for injection), and that of all FCEE and FCEA facial cleansing gel formulas, which have an irritation score of 0 (no irritation category). The study presents quantitative and qualitative data in evaluating facial skin cleansers. These results demonstrate safe formulation.